Prevalence of active and passive tobacco smoking among Beijing residents in 2011. Issue 2 (June 2016) - Zhang, Ding-Ding; Cao, Jie; Dong, Zhong; Li, Jian-Xin; Li, Gang; Ma, Ai-Jun; Yang, Xue-Li; Liu, Fang-Chao; Chen, Ji-Chun; Huang, Jian-Feng; Gu, Dong-Feng
Abstract: Objectives: This study was aimed to investigate the prevalence of active and passive tobacco smoking among Beijing residents in 2011. Methods: A cross-sectional survey was conducted, using a stratified multistage cluster random sampling method to select a representative sample of 20, 242, among Beijing residents aged 18–79 years. Active and passive tobacco smoking information was collected by a standardized and validated questionnaire in a face-to-face interview. All estimates of prevalence and numbers were weighted by the 2010 Beijing Population Census data and the sampling scheme. Results: Among Beijing residents aged 18–79 years, the overall prevalence of ever smokers and current smokers were 33.13% and 30.18%, respectively. The prevalence in males was much higher than that in females (60.75% vs . 3.75% for ever smokers, and 55.53% vs . 3.21% for current smokers, respectively). For overall current smokers, 14.12 cigarettes were consumed per day. However, only 8.91% of ever smokers quitted smoking at the time of the survey, and 2.44% of ever smokers quitted smoking in recent two years. Furthermore, 44.74% of overall nonsmokers and former smokers, with 47.03% of males and 43.63% of females, reported exposure to secondhand smoke for at least 15 minutes per day and at least one day per week. Conclusions: Tobacco smoking prevalence is still extremely high in Beijing. Nonsmokers do still suffer from secondhand smoke critically. Further urgent efforts for tobacco control are warranted in Beijing.